PENTINGNYA PEMAHAMAN PENEGAK HUKUM TENTANG PIDANA PASAR MODAL TINJAUAN KASUS BENNY TJOKROSAPUTRO - Ramadhan, Akbar; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
The actions of investigators, in this case the Attorney General’s Office in handling the case of Benny Tjokrosaputro (PT Asuransi Jiwasraya) are very aggressive and premature. In fact, there are difficulties experienced by investigators in carrying out investigations up to the prosecution stage die to a lack of understanding of capital market crimes. Investigators and prosecutors as well as the company’s level of compliance in conducting “due diligence” which is not equivalent to banks and beneficial owners further complicate the existing problems. Therefore, law enforcement of the case against Benny Tjokrosaputro must be utilized as a right time in making comprehensive improvements in the capital market sector, in terms of legislation to governance, in restoring integrity in the capital market sector in Indonesia. This study aims to analyze the inaccuracy of the verdict if the Jiwasraya Insurance corruption court with the convict Benny Tjokrosaputro, analyze the seizure of assets that are mostly registered under the name of the company PT Hanson Internasional Tbk. even though the defendant’s position in the case a quo is as a person including property obtained by the defendant before his involvement in the case a quo, and examine the inaccuracy of the imposition of punishment. The focus of the study is directed to the legal facts that are proven in the judge’s consideration and also related to the investigation process carried out by the Attorney General’s Office. Legal research is conducted systematically by examining library materials or secondary data. This research is a normative research whose method of analysis is based on ignorance and/or lack of knowledge about the trading system in the financial sector. So that it is necessary to develop special abilities for law enforcers in Indonesia so that the investigation process runs fairly.Keywords: Understanding, Law Enforcement, Crime